Free-living marine nematodes of the family Sphaerolaimidae (Chromadoria, Monhysterida) from the mangroves of the Qeshm Island, Persian Gulf - Tchesunov, Alexei V.; Eskandari, Ali; Hosseinvand, Manouchehr; Hajializadeh, Parima (Zootaxa, 2024)
Three species of the family Sphaerolaimidae were found and are described for the first time along the coast of the Qeshm Island. Sphaerolaimus qeshmensis sp. n. is characterized by large body, position of the amphideal fovea at the level of gymnostoma, rather long spicules and presence of dorso-caudal apophysis of the gubernaculum. The new species differs from related S. kleini, S. limosus, S. makrolasius and S. micropapillatus by body length, subcephalic setae length, and other fine details. Sphaerolaimus pumilus sp. n. is characterized by minute body, position of the amphideal fovea posterior to the stegostoma, and short spicules without a gubernaculum. The new species differs from the close S. paragracilis by slightly smaller subcephalic setae arranged in eight groups and total absence of even a vestigial gubernaculum. Parasphaerolaimus brevisetosus found first in mangroves of North Vietnam is redescribed with addition of some important details missed in the original diagnosis. Genera diagnoses of Sphaerolaimus and Parasphaerolaimus are emended and amended. Data on diet of the three studied species are given.